Albright's syndrome. - Tagliavanti, M.; Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Albright's disease is a rare hereditary disorder. In this article, we describe the case of a child affected by a variant of the above condition characterized by an incomplete and mild penetrance, namely by pseudo-pseudo-hypoparathyroidism with cutaneous osteoma and both statural and ponderal imbalance. Serum calcium, phosphorus and parathyroid hormone were normal, whereas alkaline phosphatase was elevated.